2002
DOI: 10.1097/00000542-200201000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Prevents Delayed Cell Death in an Organotypic Slice Culture Model of Cerebral Ischemia

Abstract: In an in vitro model of simulated ischemia, 1% isoflurane is of similar potency to 10 microm MK-801 in preventing delayed cell death. Modulation of glutamate excitotoxicity may contribute to the protective mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 0 publications
2
39
1
Order By: Relevance
“…Twenty-four hours before insult, the cultured slices were exposed to 75% xenon, 20% oxygen, and 5% carbon dioxide (or 75% nitrogen for the control group) for 45 mins at 371C (n ¼ 5 to 9/group). OGD was induced in a balanced salt solution for 2 h. Images were obtained before and 3 days after OGD to quantify dead cells with propidium iodide (PI) fluorescence; the intensity of PI fluorescence after OGD (reflective of the number of dead cells) (Sullivan et al, 2002), less the fluorescence at baseline, reflected the neuroprotective benefit derived from preconditioning. Propidium iodide intensity, corresponding to the number of dead neurons, was assessed in CA1 and dentate gyrus areas of the hippocampus by one author who was masked to the treatment groups.…”
Section: Hippocampal Slice Culturementioning
confidence: 99%
“…Twenty-four hours before insult, the cultured slices were exposed to 75% xenon, 20% oxygen, and 5% carbon dioxide (or 75% nitrogen for the control group) for 45 mins at 371C (n ¼ 5 to 9/group). OGD was induced in a balanced salt solution for 2 h. Images were obtained before and 3 days after OGD to quantify dead cells with propidium iodide (PI) fluorescence; the intensity of PI fluorescence after OGD (reflective of the number of dead cells) (Sullivan et al, 2002), less the fluorescence at baseline, reflected the neuroprotective benefit derived from preconditioning. Propidium iodide intensity, corresponding to the number of dead neurons, was assessed in CA1 and dentate gyrus areas of the hippocampus by one author who was masked to the treatment groups.…”
Section: Hippocampal Slice Culturementioning
confidence: 99%
“…As a component of our MCAO animal protocol, we used the inhalational anesthetic isoflurane for induction and maintenance of anesthesia during the ischemic period alone. We recognize that isoflurane, like other anesthetics, has been shown previously to confer protection from cerebral ischemia-reperfusion injury when delivered before ischemia (Kapinya et al, 2002;Sullivan et al, 2002). However, isoflurane was used for anesthesia in both control-treated and ␦V1-1-treated animals during the ischemic period.…”
Section: Delayed Delivery Of ␦V1-1-tat During Reperfusion Confers Promentioning
confidence: 99%
“…Research in this field may ultimately have an impact on anesthesia practice for patients with a risk of stroke. Accumulative evidence has suggested that volatile anesthetics exert neuroprotective effect when given before and after ischemia [1][2][3][4][5][6][7] . This neuroprotection is believed to occur through complex signal transduction pathways involving the activations of adenosine receptors [8,9] , protein kinase C [10][11][12][13] and mitochondrial adenosine triphosphate-regulated potassium (K ATP ) channels [2,14] .…”
Section: Introductionmentioning
confidence: 99%